Cervical screening using HPV-DNA cytology in a low-income setting: an audit within a socio-economically deprived rural community in the Philippines - Elena Harty; Samantha Carr; Zelda Doyle; Charlotte Hespe (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Cervical cancer (CC) is the second leading cause of cancer among women in the Philippines, mainly caused by a persistent human papillomavirus infection (HPV). We aimed to determine the prevalence of HPV and compare screening methods within a socio-economically deprived rural community in the Philippines. # Methods We conducted a retrospective audit of the medical records of 872 women from the free Women's clinic in a regional Philippines community over the period, 2013-2019. All participants were screened for CC using the VIA/VILI method, with only 284 women tested for HPV using the HPV-polymerase chain reaction (HPV-PCR) method. For the 284, we compared their HPV-PCR and VIA/VILI results. Data was de-identified and descriptively analysed. # Results Thirteen different HPV subtypes, all oncogenic, exist in the community. HPV was detected in 32 (11%) of the 284 women tested. Of note, 28 patients who had an oncogenic HPV infection had a normal VIA/VILI inspection result. The bivalent vaccine protects only 6% of the HPV-positive cases in the clinic. # Conclusions This study suggests HPV-PCR testing is superior at detecting HPV before cervical changes occur. The different oncogenic HPV strains reflect the low coverage of the bivalent HPV vaccination in the community -- a key area for practice and policy reforms. Further studies on the prevalence of oncogenic HPV strains will be vital in designing suitable preventive care programs for CC.